Special values of Hecke L-functions of modular forms of half-integral weight and cohomology - Kohnen, Winfried; Raji, Wissam (Research in the mathematical sciences, 2018)
We start developing a cohomology theory in the case of half-integral weight with an attempt to focus again on the connection to special values of L-functions at half-integral and integral points inside the critical strip.